Penggunaan Media Bahan Alam untuk Meningkatkan Kemampuan Mengenal Simbol Angka 1-10 Anak Usia 4-5 tahun di TK Pertiwi Gembosan Boyolali - Aning Rahayu (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
The study carried out learning improvements designed to develop children's cognitive abilities to distinguish symbols from numbers 1-10 using natural materials at the Pertiwi Gembosa Kindergarten, Bendo, Nogosari, Boyolali for 4-5 years old. The type of research used is classroom action research with the research model of Kemmis and Mc. Taggart. The research was conducted in 3 cycles. The children studied were children aged 4-5 years totaling 12 pupils, 9 boys and 3 girls. The data collection tool is observation (check list), which consists of observation sheets for pupils’ activities. Methods of collecting data through observation, interviews, and documentation. Technical analysis of the data was carried out in a qualitative descriptive manner. Success ed Indicators off study, if 80% are able to recognize the number symbols 1-10. The ability of children aged 4-5 years to recognize the number symbols 1-10 increased significantly in each cycle. Observations from the pre-action showed that 33% of children who were able and 67% of pupils were unable, the first cycle 58% of children who were able and 42% poor children, in the second cycle 75% of children who are able and 25% of pupils who cannot, the third cycle 92% are able and 8% are unable and the indicators of success have been achieved. So, it can be concluded that in TK Pertiwi Gembosan, Bendo, Nogosari, Boyolaliu, the use of natural media can improve the ability of pupils aged 4-5 years to recognize symbols numbers 1-10.